Sharpening Our Tools: A Systematic Review to Identify Diagnostically Accurate Language Sample Measures. - Ramos, Michelle N.; Collins, Penelope; Peña, Elizabeth D. (Journal of Speech, Language & Hearing Research, 2022)
Purpose: This systematic review provides a comprehensive summary of the diagnostic accuracy of English language sample analysis (LSA) measures for the identification of developmental language disorder. Method: An electronic database search was conducted to identify English publications reporting empirical data on the diagnostic accuracy of English LSA measures for children aged 3 years or older. Results: Twenty-eight studies were reviewed. Studies included between 18 and 676 participants ranging in age from 3;0 to 13;6 (years;months). Analyzed measures targeted multiple linguistic domains, and diagnostic accuracy ranged from less than 25% to greater than 90%. Morphosyntax measures achieved the highest accuracy, especially in combination with length measures, and at least one acceptable measure was identified for each 1-year age band up to 10 years old. Conclusion: Several LSA measures or combinations of measures are clinically useful for the identification of developmental language disorder, although more research is needed to replicate findings using rigorous methods and to explore measures that are informative for adolescents and across diverse varieties of English.